Program latihan kemahiran: Perbandingan kos, kebolehpasaran dan pendapatan pelatih - Awang, Abd Hair; Hamzah, Azimi; Uli, Jegak; Ahmad, Asma; Ismail, Rahmah (Universiti Utara Malaysia, 2007)
Over the last several decades, public investment in vocational training has increased substantially is strengthening implementation of a knowledge based economy, industrialisation, technology advancement and productivity. The government and international agencies proposed that the public vocational training institutions should be reviewed regularly to enhance the effectiveness of vocational traning programmes. Therefore, the main purpose of this study was to compare the costs and effectiveness of the public vocational training institutions in Malaysia. This paper examines the costs and effectiveness of vocational training progmmes organised by ILPs and IKMs. Longitudinal follow-up survey and in-depth interviews were used to achieve the central objective of this study. Respondents were selected using the proportion sampling technique and stratified according to the location of each type of institutions. The results indicated that graduates from IKMs had higher employment rates, job relevancy and current salary than graduates of ILPs.